Institutional and political determinants of private participation in infrastructure - Marian Moszoro; Gonzalo Araya; Fernanda Ruiz-Nu\~nez; Jordan Schwartz (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2014)
We assembled a large panel of project-level technical and financial data and country-level economic, institutional, political, and governance variables to assess the determinants of private financing of infrastructure in emerging markets and developing economies. Controlling for economic characteristics, we find that overall private participation of infrastructure financing increases with freedom from corruption, rule of law, quality of regulations, and decreases with court disputes. We provide plausible explanations of deviations from this pattern when data is disaggregated at the sectoral level. We also found that legal systems-types of democracy or dictatorship-do not play a role in whether the private sector invests in infrastructure. Our results do not vary when controlling for income inequality and across quartiles of experience, country wealth, and wealth per capita. The study shows that upstream "enabling" institutions, policies, and regulations and sector economics need to be addressed simultaneously to facilitate private infrastructure investment financing.
Keywords: D73; H54; L33; L51; R42; 330; Private Participation in Infrastructure; Bureaucracy; Corruption; Regulation; Rule of Law